Performance of a RED system with ammonium hydrogen carbonate solutions. Issue 48 (20th October 2016) - Bevacqua, M.; Carubia, A.; Cipollina, A.; Tamburini, A.; Tedesco, M.; Micale, G.
Abstract: The use of closed-loop salinity gradient power (SGP) technologies has been recently presented as a viable option to generate power using low-grade heat, by coupling a SGP unit with a thermally-driven regeneration process in a closed loop where artificial solutions can be adopted for the conversion of heat into power. Among these, the closed-loop reverse electrodialysis (RED) process presents a number of advantages such as the direct production of electricity, the extreme flexibility in operating conditions and the recently demonstrated large potentials for industrial scale-up. Ammonium hydrogen carbonate (NH4 HCO3 ) is a salt suitable for such closed-loop RED process thanks to its particular properties. At temperatures above 40–45°C, it decomposes into a gaseous phase containing NH3, CO2 and water. Thus, the use of NH4 HCO3 solutions for feeding a RED unit would allow their easy regeneration (after the power generation step) just using low-temperature waste heat in a purposely designed regeneration unit. This work aims at presenting an experimental investigation performed on a RED system fed with NH4 HCO3 solutions. Laboratory tests were carried out to find the best conditions for maximizing the power density and process performances of a RED unit by investigating a number of operating parameters such as fluid velocity and feed solutions concentration.